Influence of the EU on Colombian conflict - Gregůrková, Lucie; Antal, Jarolím, 1986-; Němcová, Ingeborg, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
Colombia has been suffering from internal armed conflict since the 1960s. The European Union decided to interfere in the conflict s resolution in the beginning of the millennium with several means. This thesis aims to analyse the effect of the European Union s actions on the evolution of the Colombian conflict and to consider whether it has contributed to peace in Colombia. The European Union s real actions towards Colombia will be compared firstly with recommendations of two theoretical concepts, provided by Johan Galtung and John Paul Lederach, and secondly with the legislative framework of the European Union. Even though the European Union s development efforts in Colombia were evaluated as contributing to peace in Colombia, separate actions of some European Union s Member States, organizations or citizens were found to have the opposite impact. Thus, it is advisable for the European Union to develop a framework ensuring consistency and coherence of the European Union s both internal and external activities.
Vedoucí práce: Jarolím Antal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: evropská integrace [obor dipl. práce]; diplomové práce; master's theses